Methane Mitigation and Microbial Diversity of Silage Diets Containing Calliandra calothyrsus in a Rumen in Vitro Fermentation System - R Ridwan; I Rusmana; Y Widyastuti; K G Wiryawan; B Prasetya; M Sakamoto; M Ohkuma (Media Peternakan, 2014)
This study was conducted to investigate the effects of silage based diets on methane (CH4) mitigation and microbial diversity in a rumen in vitro fermentation. The experiment was arranged in a completely randomized design with five treatments and three replications. The dietary treatments consisted of varying levels of silage containing 50% Calliandra calothyrsus as follows K; 100% concentrate + pure tannic acid of 1 mg/mL, R1; 25% silage + 75% concentrate, R2; 50% silage + 50% concentrate, R3; 75% silage + 25% concentrate, and R4; 100% silage. The fermentation variables measured were total gas, CH4, in vitro organic matter digestibility (IVOMD), VFAs, pH, N-NH3, number of protozoa, and microbial diversity analysis. Increasing level of silages reduced total gas production, CH4 concentration, IVOMD, index of bacterial diversity, protozoal number, total methanogens and Methanobacteriales population. Diet with 25% to 50% silage decreased CH4 concentration, total gas production and IVOMD by 11.43%, 24.92%, and 18.73%, respectively. Ammonia N and VFAs (except butyrate and valerate) were significantly reduced (P